2008
DOI: 10.1159/000115327
|View full text |Cite
|
Sign up to set email alerts
|

Immunologic Control for Polyomavirus Infection after Kidney Transplantation

Abstract: Aims: We compared the relative efficacy of urine decoy cell (UDC) and polymerase chain reaction (PCR) to identify polyomavirus (PV) infection, and investigate the efficacy of reduction of immunosuppression for earlier-stage PV infection before irreversible graft injury. Methods: A total of 222 de novo renal transplant recipients from March 2003 to September 2005 were enrolled. Prospective UDC monitoring with supplementary PV-PCR was performed. Early reduction of immunosuppression was guided by the results of U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Although there are no randomized controlled trials, a number of observational studies have reported successful clearance of BKV viremia in >85%. More advanced disease may require more interventional steps, a longer time for recovery and result in a permanent loss of renal function .…”
Section: Treatment Of Pyvanmentioning
confidence: 99%
“…Although there are no randomized controlled trials, a number of observational studies have reported successful clearance of BKV viremia in >85%. More advanced disease may require more interventional steps, a longer time for recovery and result in a permanent loss of renal function .…”
Section: Treatment Of Pyvanmentioning
confidence: 99%
“…Both protocols appear to be safe and effective in adult and pediatric patients for preventing PyVAN and clearing BKV viremia without excessive rates of acute rejection during follow-up (39,75). Although no randomized controlled trials have evaluated any of these strategies, a number of observational studies and case series have reported success rates of >85% (54,(76)(77)(78)(79)(80).…”
Section: Additional Strategies Have Been Switching From Tacrolimus Tomentioning
confidence: 99%
“…The presence of DCs was originally reported as negative or no DCs, a few (1-3 DCs/10 high power field [HPF] in routine smear slides or in cytospin slide), several (4-9 DCs/10 HPF in routine smear slides or in cytospin slide) and many DCs (≥10 DCs/10 HPF in routine smear slides or in cytospin slide) 6. In the current study, we classified cases with a few and several DCs into the low-grade (LG) shedding group and those with many DCs detected at least once during the study into the high-grade (HG) shedding group (Fig.…”
Section: Methodsmentioning
confidence: 99%